Realizing ultrahigh capacity quantum superdense coding on quantum photonic chip - Li, Yuan (2025)
Quantum superdense coding provides a compelling solution to enhance the channel capacity compared with classical coding, which plays a vital role in quantum networks. However, the realization of a degenerate high-dimensional entangled state with high fidelity has remained an elusive challenge, limiting improvement in channel capacity. Here, we have demonstrated a 16-mode quantum process photonic chip and experimentally validated a degenerate eight-dimensional quDit entangled state with a fidelity of 0.973±0.002. Moreover, we propose an efficient Bell state measurement method to distinguish eleven orthogonal Bell states in eight-dimensional quantum superdense coding. Leveraging the high-quality features of our quantum photonic chip, we have achieved an unprecedented channel capacity of 3.021±0.003 bits, highlighting the largest channel capacity to date. Furthermore, our method presents a remarkable quantum advantage over classical schemes, the latter of which can only transmit a maximum of 3 bits in the environment without any noise. Our findings not only open up a new avenue for integrated quantum information processing, but also contribute significantly to the advancement of multidimensional technologies, facilitating the establishment of practical, high-capacity quantum networks.